2017
DOI: 10.1111/pin.12586
|View full text |Cite
|
Sign up to set email alerts
|

Chondroblastoma of extra‐craniofacial bones: Clinicopathological analyses of 103 cases

Abstract: We elucidated clinicopathological characteristics of chondroblastoma (CB) in Japan, and reliable clinicopathologic parameters predicting local recurrence and/or metastasis. Clinicopathological profiles of 103 CB (80 male, 23 female) in extra-craniofacial bones were retrieved. Numerical scoring of nine pathological and five radiological features was statistically analyzed to determine prognostic significance. Age ranged 8-61 years (average 19.6 years). Frequently involved sites were femur, tibia, calcaneus, pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
28
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 13 publications
6
28
0
6
Order By: Relevance
“…It usually affects the epiphyses or apophyses of long bones such as humerus, femur and tibia. Less common location affected by chondroblastoma including patella, calcaneus, acetabulum and even spine, also had been reported in literature [9][10][11].It seems that chondroblastoma occurs more frequently in males than in females, in a ratio of 2.3 to 1 [2,12]. In this group of patients, the mean age of onset was 13 years old with a male to female ratio of 1.5:1, and also the proximal humerus was the mostly involved location, which all coincided with most previous studies.…”
Section: Discussionmentioning
confidence: 73%
“…It usually affects the epiphyses or apophyses of long bones such as humerus, femur and tibia. Less common location affected by chondroblastoma including patella, calcaneus, acetabulum and even spine, also had been reported in literature [9][10][11].It seems that chondroblastoma occurs more frequently in males than in females, in a ratio of 2.3 to 1 [2,12]. In this group of patients, the mean age of onset was 13 years old with a male to female ratio of 1.5:1, and also the proximal humerus was the mostly involved location, which all coincided with most previous studies.…”
Section: Discussionmentioning
confidence: 73%
“…It mostly affects the epiphyses or apophyses of long bones such as humerus, femur and tibia. Less common locations including patella, calcaneus, acetabulum and spine, also had been reported in literature [9][10][11].It seems that chondroblastoma occurs more frequently in males than in females, with a ratio of 2.3 to 1 in literature [2,12]. In our study of chondroblastoma , the mean age of onset was 13 years old with a male to female ratio of 1.5:1, and also the proximal humerus was the mostly involved location, which all coincided with most previous studies.…”
Section: Discussionmentioning
confidence: 83%
“…Considering that CB is essentially a benign bone tumor that rarely metastasizes [2,3,8,15], intralesional curettage [19]. While a component of aneurysmal bone cysts has been considered to be associated with aggressive CB [20], other studies have failed to confirm this [2,15,21].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Sailhan et al observed that epiphyseal- metaphyseal CB was not associated with a higher recurrence rate compared to epiphyseal CB [1]. Furthermore, no studies have succeeded to identify predictive pathological features for aggressive CB [19,21]. Typically, autogenous or allogeneic bone graft or polymethylmethacrylate has been used to fill the bone defect after curettage of benign bone tumor.…”
Section: Discussionmentioning
confidence: 99%